- 2x
^{2}– 3x > 4 - 4x
^{2}+ 2x < 3 - -4x
^{2}– 3x > 4 - -2x
^{2}+ 3x < -5 - 4x
^{2}– 3x > 4

The solution is #3 because all of the others have solutions

Skip to content
# Which One Does Not Belong – Inequalities and Quadratic

# Which One Does Not Belong – Trigonometric

# Which One Does Not Belong – Trigonometric

# What Does Not Belong – Linear

# Which One Does Not Belong – Misc

# Which One Does Not Belong – Linear

# Which One Does Not Belong – Misc

# Which One Does Not Belong – Quadratic

# Which One Does Not Belong – Exponential

# Which One Does Not Belong – Linear

- 2x
^{2}– 3x > 4 - 4x
^{2}+ 2x < 3 - -4x
^{2}– 3x > 4 - -2x
^{2}+ 3x < -5 - 4x
^{2}– 3x > 4

The solution is #3 because all of the others have solutions

- sin x = -1
- sin x = 0
- sin x =¼
- sin x = 1
- sin x = 2

The solution is #5 because all of the others have solutions

- tan 405°
- tan 245°
- tan 45°
- cos 360°
- cos 720°

The solution is #2 because all of the others are equivalent to 1

- 2x + 2y = 4
- -x + y = 2
- 4y = -4x + 8
- 2(x + y) = 4
- -2x – 2y = -4

The solution is #2 because all of the others are equivalent

- 2x
^{3}– 4x^{2}+2(2x^{2}) - 5x(2x)
^{3}– 4x^{2}-2(2x) - 5(2x)
^{3}– 4x^{2}-2(5x) - 12x
^{4}– 4x^{3}– 2(3x^{4}) - 2x
^{4}– 4x^{4}+ 3x^{3 }+ 2x^{4}

The solution is #2 because all of the others are cubic polynomials

- 2x + 5y = 10
- 5y = -2x – 15
- 4 – 4x = 10y
- 10y = 5x – 10
- 4x + 10y = 5

The solution is #4 because all of the other lines are parallel

- 2x + 4(3x – 2) = 13x – 3
- log 10
- sin 270°
- x
^{2}+ 2x = -1 - (-2x + 3)÷(2x – 3)

The solution is #2 because all of the others simplify to -1

- x
^{2}+ 6x + 9 - x
^{2}+ 6x + 12 - x
^{2}+ 4x + 4 - x
^{2}+ 8x + 16 - x
^{2}+ 10x + 25

The solution is #2 because all of the others are perfect square trinomials

- (xy)
^{2}(2xy)^{3} - (x
^{3}y)(x^{2})(2y)^{3} - (4x
^{3}y^{2})(2x^{2}y^{3}) - 8x
^{2}(x^{3}y^{5}) - (2x
^{2})(2y^{2})^{2}(x^{3}y)

The solution is #2 because all of the others are equivalent to 8x^{5}y^{5}

- 2x + y = 2x
- 3x – y = 4x
- 15y = 30
- 24x = 3
- y + 5x = 3x + y

The solution is #2 because all of the others form vertical or horizontal lines